2020
DOI: 10.1088/1757-899x/993/1/012007
|View full text |Cite
|
Sign up to set email alerts
|

Investigation and Analysis of Properties of Magnesium Alloy for Suitability to Electric Vehicle Components

Abstract: Magnesium is very attractive material with the combination of good strength, low weight and low corrosiveness. The uses of its alloy materials through various manufacturing methods are found in aerospace and automotive components in common inspired by weight restriction and reduction. Magnesium alloys are very light, strong and also possesses high thermal radiation properties. The high performance magnesium alloys with high temperature characteristics, pressure tightness and their ability to produce complex sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…This weight reduction greatly affects emission reduction [ 1 ], which has a positive impact on environmental factors and, moreover, will also bring benefits from an economic perspective [ 2 ]. Reflecting on recent trends, the utilization of magnesium alloys has been used in automotive components [ 3 ], and it has even been reported that several types of magnesium alloys have begun to be used in the manufacturing industry for applications in electric vehicle chassis [ 4 ] and body structures [ 5 ]; this has attracted the attention of scientists worldwide to develop magnesium-based alloys and their composites for many applications. The choice of magnesium as a potential candidate for engineering applications is due to its good castability and machinability, high specific strength, and, more uniquely, well-controlled weldability [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…This weight reduction greatly affects emission reduction [ 1 ], which has a positive impact on environmental factors and, moreover, will also bring benefits from an economic perspective [ 2 ]. Reflecting on recent trends, the utilization of magnesium alloys has been used in automotive components [ 3 ], and it has even been reported that several types of magnesium alloys have begun to be used in the manufacturing industry for applications in electric vehicle chassis [ 4 ] and body structures [ 5 ]; this has attracted the attention of scientists worldwide to develop magnesium-based alloys and their composites for many applications. The choice of magnesium as a potential candidate for engineering applications is due to its good castability and machinability, high specific strength, and, more uniquely, well-controlled weldability [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The search for lightweight construction materials that are characterized by favorable strength parameters is a topical current area of interest among scientific circles, which invariably considers magnesium alloys to be among the most important of the group of materials mentioned above. Nowadays, since electric cars make up an increasing percentage of the manufactured assortment of cars, reducing the curb weight of cars and the consumption of energy or fuel is very important for manufacturers and consumers [1][2][3][4][5][6]. Magnesium alloys, as the lightest construction material exhibiting good heat dissipation and vibration damping, have been of interest to the automotive industry for over two decades [7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The former can be accomplished by mixing in appropriate reinforcing particles with the current material. Thiagarajan et al [17] have discussed improving vehicle performance by lowering the rolling resistance and boosting the overall efficiency. Zouari et al [18], have investigated the transient hygroscopic behaviour of a 2/2 twill flax fabric-reinforced epoxy composite, a three-node membrane finite element was constructed.…”
Section: Introductionmentioning
confidence: 99%